New Methods of Studying Young Stellar Objects Using Radio Interferometry - Feeney-Johansson, Anton (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
While most studies of star formation are based on infrared or optical observations, radio astronomy has also proven very useful in the study of this process. This is seen for example in the detection of free-free emission from the jets of young stellar objects (YSOs), which has allowed us to estimate parameters such as the ionization fraction or the mass-loss-rate of these jets, or in the detection of synchrotron emission, indicating that electrons are accelerated to relativistic speeds in shocks of YSO jets. Thanks to the upgrading of radio interferometers such as the Karl G. Jansky Very Large Array (VLA) or the Enhanced Multi Element Remotely Linked Interferometer Network (e-MERLIN), and the resulting huge increase in sensitivity, there are new opportunities to apply radio astronomy to the study of star formation. As well as this, new, sensitive low-frequency radio interferometers such as the Low-Frequency Array (LOFAR) mean that there is now the possibility to study YSOs at much lower frequencies than previously possible. In my first work in Chapter 2, I report on the detection of synchrotron emission in two emission knots in the jet of the low-mass YSO DG Tau A at 152 MHz using LOFAR. In one of the knots, a low-frequency turnover in its spectrum is clearly seen compared to higher frequencies. This is the first time such a turnover has been seen in nonthermal emission in a YSO jet. I consider several possible mechanisms for the turnover and fit models for each of these to the spectrum. Based on the physical parameters predicted by each model, the Razin effect appears to be the most likely explanation. From the Razin effect fit, I obtain an estimate for the magnetic field strength within the emission knot of ~ 20 uG. If the Razin effect is responsible, this is the first time the magnetic field strength along a YSO jet has been measured based on a low-frequency turnover in nonthermal emission. Then in Chapter 3, I report the first detection of coherent emission at low frequencies from T Tauri stars. Using LOFAR, several bright radio bursts are detected at 150 MHz from two weak-line T Tauri stars: KPNO-Tau 14 and LkCa 4. All of the bursts have high brightness temperatures (10^13 - 10^14 K) and high circular polarisation fractions (60 - 90 %), indicating that they must be due to a coherent emission mechanism. This could be either plasma emission or electron-cyclotron maser (ECM) emission. Due to the exceptionally high brightness temperatures seen in at least one of the bursts (> 10^14 K), as well as the high circular polarisation levels, ECM is favoured as the most likely emission mechanism. Assuming this is the case, the required magnetic field in the emission regions would be 40 - 70 G. I determine that the most likely method of generating ECM emission is plasma co-rotation breakdown in the stellar magnetosphere. There remains the possibility, however, that it could be due to an interaction with an orbiting exoplanet. Finally in Chapter 4, I obtain high-resolution radio images of two binary YSOs: L1551 IRS 5 and L1551 NE, using e-MERLIN, the VLA, and the Atacama Large Millimeter Array (ALMA) covering a wide range of frequencies from 5 - 336 GHz. By comparing these observations to observations at a previous epoch, it is shown that there is high degree of variability in the free-free emission from the jets of these sources. In particular, the northern component of L1551 IRS 5 shows a remarkable decline in flux density of a factor of ~ 5. By fitting the spectra of the sources, the ionized mass loss rates of the jets are derived and it is shown that there is significant variability on timescales of several years. Thanks to the high resolution achieved at cm-wavelengths, it is also possible to study the launching and collimation zone in more detail. Using radiative transfer modelling, a model image is obtained for the jet of the southern component of L1551 IRS 5. By comparing this with the observed image, it was possible to estimate the collimation distance of the jet. This suggested the jet is collimated on scales of < 12 au, similar to previous upper limits for the collimation distances of jets.
APPROVED
Keywords: Radio Astronomy; Star Formation